The role of meteorological parameters on the infestation of rust and leaf miner of groundnut at Akola - CHATTOPADHYAY, N.; DUBEY, R. C.; WADEKAR, S. N. (MAUSAM, 1996)
ABSTRACT- Effect of meteorological parameters on the incidence of rust and leaf miner of groundnut at Akola, Maharashtra is studied. Both graphical and statistical methods are used as tools for evaluating correlation of meteorological parameters with rust and leaf miner. It is found that rust infestation occurs in the pod ripening stage whereas leaf miner attack extends from pod formation to pod ripening stage of groundnut. Decrease of minimum temperature, relative humidity and increases of sunshine hours a few days back increases rust infestation. Increase in maximum temperature in humid and bright sunshine condition helps to raise leafminer population.